Comparison of inhibition test of mouthwash containing chlorhexidine 0.12% and cetylpyridinium chloride 0.1% with povidone iodine 1% against Porphyromonas gingivalis: Perbandingan uji daya hambat obat kumur yang mengandung chlorhexidine 0,12% dan cetylpyridinium chloride 0,1% dengan povidone iodine 1% terhadap Porphyromonas gingivalis - Bryan Agung Sutanto; Henry Yonatan Mandalas; Vinna Kurniawati Sugiaman (Makassar Dental Journal, 2024)
Gram-negative anaerobic bacteria and microaerophilic bacteria found in the subgingival area are the cause of chronic periodonti-tis. The main bacteria causing chronic periodontitis is Porphyromonas gingivalis, which is present in 53.8% of cases. Mouthwash is a solution or liquid used to cleanse the mouth of plaque and mouth disease-causing organisms. This study was conducted to compare the inhibitory power of mouthwash containing CHX 0.12% and CPC 0.1% with povidone iodine 1% on P.gingivalis. The well diffusion test was conducted to see the most effective inhibition in inhibiting the growth of these bacteria by measuring the diameter of the inhibition zone of the clear zone formed. It was concluded that there was greater antibacterial inhibition of mouth-wash containing CHX 0.12% and CPC 0.1% than mouthwash containing povidone iodine 1% in inhibiting the growth of P.gingivalis.